2002
DOI: 10.1016/s0022-3697(02)00133-6
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of antiferromagnetism and superconductivity in heavy-fermion systems

Abstract: We report the novel pressure(P )−temperature(T ) phase diagrams of antiferromagnetism (AF) and superconductivity (SC) in CeRhIn5, CeIn3 and CeCu2Si2 revealed by the NQR measurement. In the itinerant helical magnet CeRhIn5, we found that the Néel temperature TN is reduced at P ≥ 1.23 GPa with an emergent pseudogap behavior. The coexistence of AF and SC is found in a narrow P range of 1.63 − 1.75 GPa, followed by the onset of SC with line-node gap over a wide P window 2.1 − 5 GPa. In CeIn3, the localized magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…These compounds are quasi-2D materials with the layered structure, which has been confirmed by the de Haas-van Alphen (dHvA) measurements [ 481,482,483,484,485]. The P − T phase diagram in CeRhIn 5 [ 477] and the phase diagram in the alloy system CeRh 1−x Ir x In 5 [ 486] indicate that the superconductivity appears in the neighborhood of the AF phase. The power-law behavior of the resistivity in the normal phase with T 1.3 in CeIrIn 5 (T c = 0.4K) [ 465] and T in CeCoIn 5 (T c = 2.3K) [ 466] implies the strong quasi-2D AF spin fluctuation.…”
Section: Ce-based Compoundsmentioning
confidence: 57%
See 1 more Smart Citation
“…These compounds are quasi-2D materials with the layered structure, which has been confirmed by the de Haas-van Alphen (dHvA) measurements [ 481,482,483,484,485]. The P − T phase diagram in CeRhIn 5 [ 477] and the phase diagram in the alloy system CeRh 1−x Ir x In 5 [ 486] indicate that the superconductivity appears in the neighborhood of the AF phase. The power-law behavior of the resistivity in the normal phase with T 1.3 in CeIrIn 5 (T c = 0.4K) [ 465] and T in CeCoIn 5 (T c = 2.3K) [ 466] implies the strong quasi-2D AF spin fluctuation.…”
Section: Ce-based Compoundsmentioning
confidence: 57%
“…The ground state of CeCu 2 (Si 1−x Ge x ) 2 , with increasing x, changes from the SC phase to the AF phase through the coexistent phase, owing to negative chemical pressures by Ge substitution for Si [ 476,477]. This property is similar to that of the organic superconductor, as is explained in Sec.…”
Section: Ce-based Compoundsmentioning
confidence: 65%
“…In the disordered state, T ÿ1 1 is independent of doping above 5 K and shows an unusual T 1=4 dependence. This behavior contrasts with the evolution of T ÿ1 1 with pressure in pure CeCoIn 5 , CeRhIn 5 , CeIn 3 , and CeCu 2 Si; Ge 2 , where the magnitude of T ÿ1 1 in the disordered state changes dramatically as the ground state evolves from antiferromagnetic to superconducting [15,16]. Pressure tuning modifies the Kondo interaction, J, and changes in the ground state are reflected in T ÿ1 1 through modifications of the spin fluctuation spectrum.…”
Section: Prl 99 146402 (2007) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 86%
“…13 predicts that the ordering wave vectors take discrete values that correspond to different Mott insulating PDW lobes. For long-range interactions, PDW phases are very densely packed, so experimentally we may observe an almost continuous dependence of incommensuration on doping, such as the one discussed by Yamada et al ͑1998͒ Kitaoka et al, 2002. and Wakimoto et al ͑2000͒. However, different states in the hierarchy are not equivalent.…”
Section: Global Phase Diagram and Multicritical Pointsmentioning
confidence: 89%
“…Noting that D = D Si ͓1͑V Ge − V Si ͒x / V Ge ͔ for Ge doping and that D increases with pressure, one can draw a combined phase diagram as a function of lattice density D ͑Kitaoka et al, 2002͒. Kitaoka et al ͑2002͒ showed that the phase diagram of Fig. 46 could be understood in terms of an SO͑5͒ superspin picture.…”
Section: Uniform Mixed Phase Of Antiferromagnetism and Superconducmentioning
confidence: 99%